Beyond the New perspective - Buch-Hansen, Gitte (Studia theologica, 2017)
Krister Stendahl's famous 1963 Harvard Theological Review article, "The Apostle Paul and the Introspective Conscience of the West", is often seen as the kick-starter of the New Perspective on Paul. According to Stendahl, Protestantism could not trace its theological roots to the Pauline correspondence. Dogmatic reflections on the human condition had to await a figure like Augustine, whose elaborate theology complied with the new situation of the church as the official religion of the Empire. Nevertheless, in order to argue his case as a missionary among Jews and Gentiles, Paul was informed by the discussions of the human condition that characterized Hellenistic Judaism. A glance at Philo's writings will help us to identify the problems to which Paul saw the Christ-event as the solution. Scholars are aware that in De opificio mundi - in his interpretation of the generation of the first woman and her fatal encounter with the snake (Opif. 152, 161) - Philo engages with the discussions among the various philosophical schools of his time about the character of the primary driver of human action. In this exposition, which links the desire for pleasure with generation - and consequently with the flesh - we find a preconception of Augustine's doctrine of original sin. The present essay argues that anthropological ideas similar to those found in Philo's treatises also influenced the arguments in Paul's letters - above all Rom 7 and Gal 2. Consequently, some of the "truisms" of the New Perspective - and, especially, those of the radical branch of it - must be revisited and revised.